2016
DOI: 10.1007/s00540-016-2266-2
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors for surgical site infection after cesarean delivery in a rural tertiary care medical center

Abstract: Background We aimed to determine the incidence of surgical site infection (SSI) after cesarean delivery (CD) and identify the risk factors in a rural population. Methods We identified 218 SSI patients by International Classification of Disease codes and matched them with 3131 parturients (control) from the electronic record database in a time-matched retrospective quality assurance analysis. Results and discussion The incidence of SSI after CD was 7.0 %. Risk factors included higher body mass index (BMI) [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
4
13
0
2
Order By: Relevance
“…Our findings are in accordance with risk factors known to be adversely associated with healing following surgical interventions, such as obesity, urgent CD, and chorioamnionitis 3,8. However, they partly differ from those of Vallejo et al,24 who found that high BMI, low education, parity, tobacco use, hypertension, urgent CD, and GDM were risk factors for wound infection, while PPROM was protective. The presence of PPROM was positively associated with the development of wound healing problems, while diabetes was not, although it is known to be a risk factor for the development of surgicalF I G U R E 2 Rates of wound healing problems 6 wk following CD in the context of various obstetric complications.…”
supporting
confidence: 88%
“…Our findings are in accordance with risk factors known to be adversely associated with healing following surgical interventions, such as obesity, urgent CD, and chorioamnionitis 3,8. However, they partly differ from those of Vallejo et al,24 who found that high BMI, low education, parity, tobacco use, hypertension, urgent CD, and GDM were risk factors for wound infection, while PPROM was protective. The presence of PPROM was positively associated with the development of wound healing problems, while diabetes was not, although it is known to be a risk factor for the development of surgicalF I G U R E 2 Rates of wound healing problems 6 wk following CD in the context of various obstetric complications.…”
supporting
confidence: 88%
“…Pre-operative conditions such as prolonged labor, prolonged rupture of membrane (PROM), more than 5 digital vaginal examination, chorio-amnionitis, American society of Anesthesiologist (ASA) health status classification ≥3, fewer years of education, higher prior births, prior diagnosis of hypertension and Diabetes Mellitus (DM) were identified as significant factors for SSI following CDs [10, 15, 16, 1922]. Similarly intra operative conditions like prolonged duration of surgery, wound contamination class III, vertical skin incision and interrupted skin suturing were associated factors for developing SSI [8, 9, 15, 16, 19, 23, 24]. CD for emergency conditions like non-reassuring fetal heart rate pattern (NRFHRP) was also significantly associated factor for developing SSI [19, 24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly intra operative conditions like prolonged duration of surgery, wound contamination class III, vertical skin incision and interrupted skin suturing were associated factors for developing SSI [8, 9, 15, 16, 19, 23, 24]. CD for emergency conditions like non-reassuring fetal heart rate pattern (NRFHRP) was also significantly associated factor for developing SSI [19, 24, 25]. In addition, Postoperative anemia was also found to be a post-operative factor associated with SSI [16, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients treated at West Virginia University Hospital are from rural West Virginia and have many of the inequities associated with that population. 9 Our primary objective was to examine the existing attitudes and knowledge of medical professionals in the care and treatment of transgender individuals within a rural tertiary care center. As a secondary outcome, we compared results from two cohorts that provide medical services at WVU: residents and faculty physician providers.…”
Section: Introductionmentioning
confidence: 99%